Holographic Manipulation of Nanostructured Fiber Optics Enables Spatially‐Resolved, Reconfigurable Optical Control of Plasmonic Local Field Enhancement and SERS. Issue 23 (4th May 2022) - Collard, Liam; Pisano, Filippo; Zheng, Di; Balena, Antonio; Kashif, Muhammad Fayyaz; Pisanello, Marco; D'Orazio, Antonella; de la Prida, Liset M; Ciracì, Cristian; Grande, Marco; De Vittorio, Massimo; Pisanello, Ferruccio
Abstract: Integration of plasmonic structures on step‐index optical fibers is attracting interest for both applications and fundamental studies. However, the possibility to dynamically control the coupling between the guided light fields and the plasmonic resonances is hindered by the turbidity of light propagation in multimode fibers (MMFs). This pivotal point strongly limits the range of studies that can benefit from nanostructured fiber optics. Fortunately, harnessing the interaction between plasmonic modes on the fiber tip and the full set of guided modes can bring this technology to a next generation progress. Here, the intrinsic wealth of information of guided modes is exploited to spatiotemporally control the plasmonic resonances of the coupled system. This concept is shown by employing dynamic phase modulation to structure both the response of plasmonic MMFs on the plasmonic facet and their response in the corresponding Fourier plane, achieving spatial selective field enhancement and direct control of the probe's work point in the dispersion diagram. Such a conceptual leap would transform the biomedical applications of holographic endoscopic imaging by integrating new sensing and manipulation capabilities. Abstract : A spatiotemporal method to activate either a subregion or entire plasmonic structure fabricated on the output facet of a multimode optical fiber is described for two intrinsically different classes of structures. Spatially resolved extraordinary optical transmission, surface enhanced Raman spectroscopy and control of the dispersive properties are all demonstrated as potential applications.